Type 1 cannabinoid receptor (CB1)-containing axons innervate hypophysiotropic thyrotropin-releasing hormone-synthesizing neurons - Deli Levente; Wittmann Gábor; Kalló Imre; Lechan RM; Watanabe M; Liposits Zsolt; Fekete Csaba (ENDOCRINOLOGY, 2009)
Hypophysiotropic thyrotropin-releasing hormone (TRH)-synthesizing neurons of the hypothalamic paraventricular nucleus (PVN) have a critical role in the regulation of the energy homeostasis through control of the hypothalamic-pituitary-thyroid axis. Recently, endocannabinoids have been shown to exert inhibitory effects on TRH neurons via the type 1 cannabinoid receptor (CB1). To understand the anatomical basis for this regulatory mechanism, we determined whether CB1 is contained in axons innervating hypophysiotropic TRH neurons using a recently developed antiserum against the C-terminal portion of mouse CB1. CB1-immunoreactive (IR) axons innervated densely the parvicellular subdivisions of the PVN where the hypophysiotropic TRH neurons are located. By double-labeling immunocytochemistry, CB1-IR varicosities were observed in juxtaposition to the vast majority of TRH neurons in the PVN. At the ultrastructural level, CB1-immunoreactivity was observed in the pre-terminal portion of axons establishing both symmetric and asymmetric synaptic specializations with the perikarya and dendrites of TRH neurons in the PVN. These data demonstrate that CB1 is abundantly present in axons that are in synaptic association with hypophysiotropic TRH neurons indicating an important role for endocannabinoids in the regulation of the hypothalamic-pituitary-thyroid axis. The presence of both symmetric and asymmetric type CB1 synapses on TRH neurons in the PVN suggests that endocannabinoids may influence both excitatory and inhibitory inputs of these neurons.